Developing Public Speaking Skill Through the Moslem Scholar Program in Education Management - Sureni, Sureni; Mansyur, Kurniawan; Khotimah, Adilia Khusnul; Arifiani, Bilqis Fathimatus (Universitas Islam Negeri Raden Intan Lampung, 2023)
The flagship program at Islamic educational institution aims to improve interpersonal and intrapersonal skills of the members, one of which is Moslem Scholar program at SMP Bina Insan Mandiri. The program is focused on teaching public speaking skill from early age. It is expected that the students will be able to deliver Islamic teachings, master Tsaqofah Islamiyah and have the ability to understand the sources of Islamic law well. Therefore, their religious knowledge will be beneficial for the society, both for social and religious activities. It is also expected that the society will understand human beings role as religious beings who have noble characters. This research was conducted by analyzing a case study of the Moslem Scholar flagship program at SMP Bina Insan Mandiri. This research method used descriptive qualitative research through observations and interviews. The results showed that the Moslem Scholar program at SMP Bina Insan Mandiri was carried out through a talent-screening program to accommodate students' interests. This activity aimed at increasing the quality of SMP Bina Insan Mandiri students as well as provisioning the skill to be implemented in the society.